A study of swallowing difficulties in first degree relatives of patients with achalasia. Issue 5 (May 1985) - Mayberry, J F; Atkinson, M
Abstract : Of 167 patients with achalasia asked to provide details of swallowing difficulties among their first degree relatives, 159 completed the survey (95% response rate). One thousand and twelve first degree relatives were identified, and 14 were reported to have dysphagia including two with reported achalasia. Review of the case notes of these 14 relatives showed, however, that in none was achalasia confirmed. Heartburn affected 54 (5%) of the relatives, an incidence similar to that in the general population. These findings suggest that adult achalasia is not inherited in an autosomal recessive manner and that environmental factors during early life do not play an important aetiological part.